Anterior hepatic transection for caudate lobectomy - Eleazar Chaib; Marcelo A F Ribeiro Jr; Yngrid Ellyn Dias Maciel de Souza; Luiz Augusto C D'Albuquerque (Clinics, 2009)
Resection of the caudate lobe (segment I- dorsal sector, segment IX- right paracaval region, or both) is often technically difficult due to the lobe's location deep in the hepatic parenchyma and because it is adjacent to the major hepatic vessels (e.g., the left and middle hepatic veins). A literature search was conducted using Ovid MEDLINE for the terms "caudate lobectomy" and "anterior hepatic transection" (AHT) covering 1992 to 2007. AHT was used in 110 caudate lobectomies that are discussed in this review. Isolated caudate lobectomy was performed on 28 (25.4%) patients, with 11 case (11%) associated with hepatectomy, while 1 (0.9%) was associated with anterior segmentectomy. Complete caudate lobectomy was performed on 82 (74.5%) patients. Hepatocellular carcinoma was observed in 106 (96.3%) patients, while 1 (0.9%) had hemangioma and 3 (2.7%) had metastatic caudate tumors. AHT was used in 108 (98.1%) caudate resections, while AHT associated with a right-sided approach was performed in 2 (1.8%) cases. AHT is recommended for tumors located in the paracaval portion of the caudate lobe (segment IX). AHT is usually a safe and potentially curative surgical option.